Microhematuria at Point of Care. Issue 1 (2017) - Tedesco, Martina; Casati, Lorenzo; Cozzi, Silvia; Vignati, Barbara; Civita, Federica; Clementi, Ilaria; Gambaretti, Matteo; Magistrelli, Elio; Magistri, Simone; Monticelli, Pietro; Paganuzzi, Marco Maria; Santovito, Luca Spiro; et al.
The case of a 35-year-old man presenting microscopic hematuria allows the following topics to be examined in depth: 1. How is hematuria defined and classified? 2. What are the causes of hematuria? 3. Hematuria is an important sign for the diagnosis of cancer of the urinary system. What are the risk factors for bladder carcinoma? 4. What is the role of the urinary dipstick test in the diagnosis of hematuria? 5. What is the role of the examination of urine sediment in the diagnosis of hematuria? 6. Once microscopic hematuria is confirmed, how can we proceed to reach a final diagnosis?